Synthesis of 1H-pyrazolo[3,4-b]pyridine analogues - Yen Nguyen; Greg Petruncio; Schroeder M. Noble; Mikell Paige (Results in Chemistry)
Many compounds containing the pyrazolo[3,4-b]pyridine scaffold have been found to have various pharmacological activities such as anticancer, anti-inflammatory, anti-bacterial, antihyperglycemic, and anxiolytic properties. In general, low water solubility often hinders bioassay screening of small molecules. In this work, we have prepared a series of 1H-pyrazolo[3,4-b]pyridine-4-carboxylic acid analogues through the condensation of 5-aminopyrazoles with aromatic aldehydes and pyruvic acid. We then converted the carboxylic acid handle on these heterocycles into the corresponding sodium salt, which improved the water solubility.